Transformation of the culture of the senses in the age of speed - Filina, Iryna (Actual Problems of Mind, 2017)
The article examines the negative impact of increasing the pace and speed of life in many aspects and manifestations on the culture of the senses. The author substantiates the idea that modern civilization with its speeds and conveniences comes into conflict with culture as a measure of human development.